Influence of genetic polymorphisms of styrene-metabolizing enzymes on the levels of urinary biomarkers of styrene exposure. Issue 2 (4th March 2015) - Carbonari, Damiano; Mansi, Antonella; Proietto, Anna Rita; Paci, Enrico; Bonanni, Rossana Claudia; Gherardi, Monica; Gatto, Maria Pia; Sisto, Renata; Tranfo, Giovanna
Graphical abstract: Highlights: CYP2E1*5B/*6 heterozygotes excrete less urinary styrene metabolites than wild type. Subjects carrying the EPHX1 (codon 113) exhibit reduced urinary [MA + PGA]. Urinary [MA + PGA] is modulated by predicted epoxide hydrolase activity. Styrene individual metabolic variability could lead to underestimation of exposure. Abstract: Styrene exposure is still present in different occupational settings including manufacture of synthetic rubber, resins, polyesters and plastic. The aim of this work was to investigate the effects of polymorphic genes CYP2E1, EPHX1, GSTT1, and GSTM1 on the urinary concentrations of the styrene metabolites mandelic acid (MA), phenylglyoxylic acid (PGA) and on the concentration ratios between (MA + PGA) and urinary styrene (U-Sty) and airborne styrene (A-Sty), in 30 workers from two fiberglass-reinforced plastic manufacturing plants and 26 unexposed controls. Personal air sampling and biological monitoring results revealed that sometimes exposure levels exceeded both the threshold limit value (TLV) and the biological exposure index (BEI) suggested by the American Conference of Governmental Industrial Hygienists. A significantly reduced excretion of styrene metabolites (MA + PGA) in individuals carrying the CYP2E1*5B and CYP2E1*6 heterozygote alleles, with respect to the homozygote wild type, was observed only in the exposed group. A reduction was also detected, in the same group, in subjects carrying the slow allele EPHX1 (codon 113), through the lowering of (MA + PGA)/urinary styrene concentration ratio. In addition, the ratio between MA + PGA and the personal airborne styrene concentration appeared to be modulated by the predicted mEH activity, in the exposed group, as evidenced by univariate linear regression analysis. Our results confirm some previous hypotheses about the role of the polymorphism of genes coding for enzymes involved in the styrene detoxification pathway: this may significantly reduce the levels of excreted metabolites and therefore it must be taken into account in the interpretation of the biological monitoring results for occupational exposure.